Formation of double emulsion micro-droplets in a microfluidic device using a partially hydrophilic–hydrophobic surface. Issue 56 (3rd November 2021) - Kamnerdsook, Ampol; Juntasaro, Ekachai; Khemthongcharoen, Numfon; Chanasakulniyom, Mayuree; Sripumkhai, Witsaroot; Pattamang, Pattaraluck; Promptmas, Chamras; Atthi, Nithi; Jeamsaksiri, Wutthinan
Abstract : (a) Droplet encapsulation efficiency & inner and outer diameters of water-in-oil-in-water droplets at various frequency ratios and flow rate ratios and (b) Images of water-in-oil-in-water droplets over a frequency-ratio range of fr = 0.73–1.30 Abstract : The objective of this paper is to propose a surface modification method for preparing PDMS microfluidic devices with partially hydrophilic–hydrophobic surfaces for generating double emulsion droplets. The device is designed to be easy to use without any complicated preparation process and also to achieve high droplet encapsulation efficiency compared to conventional devices. The key component of this preparation process is the permanent chemical coating for which the Pluronic surfactant is added into the bulk PDMS. The addition of Pluronic surfactant can modify the surface property of PDMS from a fully hydrophobic surface to a partially hydrophilic–hydrophobic surface whose property can be either hydrophilic or hydrophobic depending on the air- or water-treatment condition. In order to control the surface wettability, this microfluidic device with the partially hydrophilic–hydrophobic surface undergoes water treatment by injecting deionized water into the specific microchannels where their surface property changes to hydrophilic. This microfluidic device is tested by generating monodisperse water-in-oil-in-water (w/o/w) double emulsion micro-droplets for which the maximum droplet encapsulation efficiency of 92.4% is achieved with the average outer and inner diameters of 75.0 and 57.7 μm, respectively.